2019
DOI: 10.1002/ppp3.33
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for answers: Linking lectures with the real world using a mobile treasure hunt app

Abstract: Societal Impact Statement Plants underpin our society providing food, fuel, medicines, clean air and water, positive mental health, and are central to biodiversity conservation. Despite this importance and an increasing need for people with plant‐identification skills, many societies are becoming increasingly ignorant to the species with which they interact. To benefit both our undergraduates and the society they will enter, we applied mobile technology to improve plant identification and appreciation, while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Multimodal approaches to teaching and learning science have been shown to be effective in engaging students (Ainsworth, Prain, & Tytler, 2011;Hartman, Lydon, & Rasmussen, 2019;Jewitt, Kress, Ogborn, & Tsatsarelis, 2001). Furthermore, science teaching appears to benefit from varied language practices through the use of metaphors and analogies, stories and models (e.g., Jewitt et al, 2001;Matruglio, Maton, & Martin, 2013;Wilson & Mant, 2011).…”
Section: Introduction and Backg Roundmentioning
confidence: 99%
“…Multimodal approaches to teaching and learning science have been shown to be effective in engaging students (Ainsworth, Prain, & Tytler, 2011;Hartman, Lydon, & Rasmussen, 2019;Jewitt, Kress, Ogborn, & Tsatsarelis, 2001). Furthermore, science teaching appears to benefit from varied language practices through the use of metaphors and analogies, stories and models (e.g., Jewitt et al, 2001;Matruglio, Maton, & Martin, 2013;Wilson & Mant, 2011).…”
Section: Introduction and Backg Roundmentioning
confidence: 99%
“…There is then the Actionbound application, with examples based on a virtual walk through the city while solving set tasks at certain stations (bounds), which was researched by Parsons et al (2019) who have concluded that the mentioned application can be used by new students for better spatial orientation in school or another environment as well as a rich source for cultural discussion. Hartman et al (2019) emphasize that with the Actionbound app, almost all students enjoyed every moment, especially outdoor classes outside the classroom.…”
Section: The Relation Between Mobile Learning and Language Skillsmentioning
confidence: 99%
“…In this issue, Hartman et al and Lampert et al demonstrate the effectiveness of testing ideas concerning how we bring plants to student attention, whether these ideas and activities involve higher education biology students (Hartman, Lydon, & Rasmussen, ; in this issue, pp. 233) or science education secondary students (Lampert, Scheuch, Pany, Müllner, & Kiehn, ; in this issue, pp.…”
Section: Making Plants Public: Marquee Plantsmentioning
confidence: 99%
“…Furthermore, in our human engagement with this difference it is important that we do not seek to subject plants to "terms of resemblance", anchored by "the human" Houle (2011, p. 95) but rather to engage with their "plantiness" (Fleming, 2017). student attention, whether these ideas and activities involve higher education biology students (Hartman, Lydon, & Rasmussen, 2019; in this issue, pp. 233) or science education secondary students (Lampert, Scheuch, Pany, Müllner, & Kiehn, 2019; in this issue, pp.…”
Section: Mak Ing Pl Ants Pub LI C : Marquee Pl Antsmentioning
confidence: 99%